Entrepreneurship Perception and Entrepreneurship Intention in Form 4 Pupil Towards Self-Employability - Zaini, Nuradiana; Liew Abdullah, Nurul Hidayah (Online Journal for TVET Practitioners, 2025)
Entrepreneurship is the ability and readiness to develop, organize and run a business enterprise, along with any of its uncertainties in order to make a profit. Recently, entrepreneurship gained attention in terms of the development in economics. However, there have been some issues that younger generations prefer to have a career in non related entrepreneurship and consider it better than entrepreneurship. This study aims to investigate entrepreneurship perception and intention towards self- employability. A method connected to entrepreneurship was done to focus entrepreneurship education, particularly among younger generations. To address this issue, this study investigates the entrepreneurship perception and entrepreneurship intentions towards self-employability. The research design in this study is a survey and quantitative approach used in this study and the survey conducted through distribution of questionnaires. This study involves 97 samples of Form 4 pupils. In this study, analysis of frequency distribution, percentage distribution, mean, standard deviation and Pearson Correlation analysis used. The result showed that entrepreneurship perception and entrepreneurship intention towards self- employability are moderate. Besides that, the relationship between entrepreneurship perception and entrepreneurship intention in Form 4 pupils towards self- employability is moderate. Thus, good entrepreneurship perception resulted in the pupils to have the intention to own a business in the future. The research outcome can be used as a reference for the future entrepreneurship study.